Serum uric acid levels and inflammatory markers with respect to dipping status: A retrospective analysis of hypertensive patients with or without chronic kidney disease. (17th August 2016) - Ahbap, Elbis; Sakaci, Tamer; Kara, Ekrem; Sahutoglu, Tuncay; Koc, Yener; Basturk, Taner; Sevinc, Mustafa; Akgol, Cuneyt; Hasbal, Barıs; Isleem, Mahmoud; Nazif, Perin; Caglayan, Feyza Bayraktar; et al.
ABSTRACT: Background : The aim of this study was to evaluate serum uric acid levels, inflammatory markers [C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR)] and mean platelet volume (MPV) among hypertensive patients with or without chronic kidney disease (CKD) with respect to dipping status. Methods : A total of 432 hypertensive patients with ( n = 340) or without ( n = 92) CKD who had ambulatory blood pressure monitoring recordings were included. Correlation of serum uric acid levels with inflammatory markers (CRP, PLR, NLR) was evaluated as was the logistic regression analysis for determinants of nondipper pattern. Results : Nondipper pattern was noted in 65.2% and 79.7% of non-CKD and CKD patients, respectively. Multivariate logistic regression analysis revealed that only serum uric acid (OR, 2.69; 95% CI, 1.60 to 4.52; p = 0.000), MPV (OR, 1.81; 95% CI, 1.30 to 2.53; p = 0.000), PLR (OR, 0.98; 95% CI, 0.97 to 0.99; p = 0.000), and serum albumin (OR, 0.42; 95% CI, 0.19 to 0.93; p = 0.031) were significant determinants of nondipper pattern in the overall study population. Conclusion : In conclusion, our findings revealed higher prevalence of nondipper pattern in hypertensive patients with than without CKD and significantly higher levels for uric acid, CRP, MPV, PLR, and NLR among nondipper than dipper hypertensive patients with CKD. High levels for uric acid and MPV and lower levels for PLR and serum albumin were noted as significant determinants of nondipper pattern among hypertensive patients.